Bedload transport: a walk between randomness and determinism. Part 1. The state of the art - Ancey, Christophe (Journal of hydraulic research, 2020)
This paper outlines the various approaches used to calculate bedload transport. As bedload transport exhibits considerable spatial and temporal variations, computing the bedload transport rates and morphological changes experienced by streambeds is difficult. A large body of experimental work has revealed scaling laws relating the mean transport rate to hydraulic conditions (that is, water discharge , bottom shear stress or stream power ω): , or . The most common approach used to calculate bedload transport has thus long involved determining the one-to-one function (or any other dependence of on or ω) from experiments or theoretical considerations. However, the predictive power of such relationships is limited: scientists are unable to predict to within better than one order of magnitude, and morphodynamic models based on fail to explain the development of bedforms without the use of additional assumptions. Progressively, other calculation approaches have appeared, with many relying on the idea that bedload transport is a macroscopic transport process that primarily reflects random particle motion at the grain scale. The present paper reviews the main ideas being explored today.